2011
DOI: 10.1007/978-3-642-23765-2_31
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Tabletop Interface on the Co-construction of Concept Maps

Abstract: Concept Mapping is a method for externalizing and reflecting knowledge about real world phenomena. In cooperative settings, concept maps can also be used to aid cooperative learning activities and the development of a common understanding about the mapping subject. This process imposes requirements on tool support that have hardly been addressed in existing concept mapping tools. We present a tabletop interface designed to meet these requirements. In an empirical study, the positive effects on the cooperative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 13 publications
0
11
0
4
Order By: Relevance
“…This study served as a useful proof-of-concept, but it also highlighted problems such as slow object tracking, and restrictions adding new content; these suggest possible scalability problems when working with larger maps. This scalability problems were confirmed in a more recent study [24] by Oppel and Stary comparing the use of tabletop systems for concept mapping with screen based equivalents. Despite the scalability problems, the study found that the time spent on discussion was significantly higher for tabletop concept maps, and information was less likely to be filtered by 'operators' running the software tool to support the concept mapping process.…”
Section: Sensemaking and Concept Mappingmentioning
confidence: 58%
“…This study served as a useful proof-of-concept, but it also highlighted problems such as slow object tracking, and restrictions adding new content; these suggest possible scalability problems when working with larger maps. This scalability problems were confirmed in a more recent study [24] by Oppel and Stary comparing the use of tabletop systems for concept mapping with screen based equivalents. Despite the scalability problems, the study found that the time spent on discussion was significantly higher for tabletop concept maps, and information was less likely to be filtered by 'operators' running the software tool to support the concept mapping process.…”
Section: Sensemaking and Concept Mappingmentioning
confidence: 58%
“…Prior research shows that cooperative modeling task can draw benefits from the use of tabletop interfaces in co-located settings [20]. The observations made in the present work indicate that using distributed tabletops for modeling not only is able to solve the problem of restricted modeling space but also can provide added value for the modeling task itself.…”
Section: Discussionmentioning
confidence: 70%
“…Metasonic GmbH, a German business process management vendor, has implemented a complete process management suite called Metasonic Suite and a process elicitation tool called Metasonic Touch, developed from a previous university research project (Oppl and Stary 2011). Metasonic sought to engage with researchers at QUT to explore new areas of innovation around the effectiveness of their software tools.…”
Section: 1mentioning
confidence: 99%
“…The goal of the proposed research was to use 3D virtual worlds as a means of extracting process information from stakeholders in line with S-BPM concepts. Rather than use traditional modelling elicitation techniques which heavily tax the analyst (such as interviews), or using an abstract representation and interface, such as the Metasonic touch (Oppl and Stary 2011), QUT wished to explore the idea of using 3D virtual world models of workplaces as elicitation environments. Such an approach was designed with the intention to reduce the training time and complexity of modelling by providing a more natural modelling interface.…”
Section: 1mentioning
confidence: 99%